PENGARUH PROFITABILITAS, ASET TETAP, DAN PERTUMBUHAN PENJUALAN TERHADAP UTANG JANGKA PANJANG PERUSAHAAN (Studi Empiris Pada Perusahaan Ritel yang Terdaftar di Bursa Efek Indonesia Tahun 2016-2018) - Muhammad Yasir Anhar; Waeni Kusdiyanti (Jurnal Gici Jurnal Keuangan dan Bisnis, 2021)
Intense competition between companies, especially retail companies, causes companies to carry out economic activities and manage the functions contained in the company effectively. A company is able to develop its business with funding sources in the form of long-term debt. Funding decisions are important decisions that will directly determine a company's ability to survive and thrive. The factors that affect long-term debt taking include profitability, fixed assets and sales growth. This research method is quantitative with a sampling technique using side purposive and obtained samples of 11 companies. The results of the regression test showed that 15.6% of long-term debt decision factors could be explained by profitability, fixed assets and long-term debt, while the remaining 84.4% was explained by other factors not studied in this study. The F test results show that simultaneously the variables profitability, fixed assets and sales growth have no significant effect on long-term debt. The results of the T test show that partially these three variables have no effect on the long-term debt of retail companies listed on the IDX.